2013
DOI: 10.1371/journal.pone.0062780
|View full text |Cite
|
Sign up to set email alerts
|

Specific IgG Response against Mycobacterium avium paratuberculosis in Children and Adults with Crohn’s Disease

Abstract: Background and AimsPresence of serum antibodies against Mycobacterium avium paratuberculosis (MAP) in Crohn’s Disease (CD) as a disease characteristic remains controversial. In the present work, we assessed antibody reactivity of serum and intestinal fluid against four distinct MAP-antigens, including the recently identified MAP-specific lipopentapeptide (L5P).MethodsImmunoglobulin concentrations and specificity against 3 non MAP-specific antigens: glycosyl-transferase-d (GSD), purified protein derivative from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…The two studies (four lines) that reported results from sodium dodecyl sulfate (SDS) immunoblot had an overall OR of 25·01 (95% CI 12·55–49·85, I 2 = 43%; Table 2). Four other studies reported significant associations with reactivity to M. paratuberculosis [7578], four reported no significant association [7982] and one reported contradictory associations between children and adults with CD [83] (Table 2). Three studies were excluded from this summary because no reaction to M. paratuberculosis occurred [63], only CD patients were tested [84] and results were not reported separately for CD and ulcerative colitis patients [85].…”
Section: Resultsmentioning
confidence: 99%
“…The two studies (four lines) that reported results from sodium dodecyl sulfate (SDS) immunoblot had an overall OR of 25·01 (95% CI 12·55–49·85, I 2 = 43%; Table 2). Four other studies reported significant associations with reactivity to M. paratuberculosis [7578], four reported no significant association [7982] and one reported contradictory associations between children and adults with CD [83] (Table 2). Three studies were excluded from this summary because no reaction to M. paratuberculosis occurred [63], only CD patients were tested [84] and results were not reported separately for CD and ulcerative colitis patients [85].…”
Section: Resultsmentioning
confidence: 99%
“…For faecal IgA and polymeric immunoglobulin receptor (pIgR) assays, faecal proteins were extracted mechanically in complete antiprotease cocktail (Roche) and frozen at −80 °C. IgA and pIgR concentrations were measured as described previously with sheep anti-mouse IgA (Sigma) or for coating and horseradish-peroxidase (HRP)-conjugated goat anti-mouse IgA (Sigma) for revelation 64 .…”
Section: Methodsmentioning
confidence: 99%
“…In the last years, analyses of mycobacterial genomes permitted to indentify the production of lipopentapeptide (L5P) in MAP as a distinctive feature among subspecies [ 13 ]. Studies in MAP-infected ruminants showed a strong immunogenicity of L5P [ 14 ] and, more recently, highly specific IgG responses to L5P were verified in patients affected by Crohn’s disease [ 15 ].…”
Section: Introductionmentioning
confidence: 99%